DNA virome composition of two sympatric wild felids, bobcat (Lynx rufus) and puma (Puma concolor) in Sonora, Mexico - Payne, Natalie; Combrink, Leigh; Kraberger, Simona; Fontenele, Rafaela S.; Schmidlin, Kara; Cassaigne, Ivonne; Culver, Melanie; Varsani, Arvind; Van Doorslaer, Koenraad (Frontiers in Ecology and Evolution, 2023)
With viruses often having devastating effects on wildlife population fitness and wild mammals serving as pathogen reservoirs for potentially zoonotic diseases, determining the viral diversity present in wild mammals is both a conservation and One Health priority. Additionally, transmission from more abundant hosts could increase the extinction risk of threatened sympatric species. We leveraged an existing circular DNA enriched metagenomic dataset generated from bobcat (Lynx rufus, n = 9) and puma (Puma concolor, n = 13) scat samples non-invasively collected from Sonora, Mexico, to characterize fecal DNA viromes of each species and determine the extent that viruses are shared between them. Using the metaWRAP pipeline to co-assemble viral genomes for comparative metagenomic analysis, we observed diverse circular DNA viruses in both species, including circoviruses, genomoviruses, and anelloviruses. We found that differences in DNA virome composition were partly attributed to host species, although there was overlap between viruses in bobcats and pumas. Pumas exhibited greater levels of alpha diversity, possibly due to bioaccumulation of pathogens in apex predators. Shared viral taxa may reflect dietary overlap, shared environmental resources, or transmission through host interactions, although we cannot rule out species-specific host-virus coevolution for the taxa detected through co-assembly. However, our detection of integrated feline foamy virus (FFV) suggests Sonoran pumas may interact with domestic cats. Our results contribute to the growing baseline knowledge of wild felid viral diversity. Future research including samples from additional sources (e.g. prey items, tissues) may help to clarify host associations and determine the pathogenicity of detected viruses.